Importált kórokozók jelentősége avokádón (Persea americana Hass.) - Szendrei , Lilla; Petróczy , Marietta; Ágoston , János; Tóth , Annamária (GEORGIKON FOR AGRICULTURE, 2023)
Many pathogens could arrive with imported fruit and vegetables. Avocados (Persea americana Hass.) from tropical areas are very popular in Hungary, but often show symptoms caused by plant pathogens. We aimed to identify pathogens based on morphological characteristics and partial sequence of the ITS genomic region. We confirmed the presence of Colletotrichum, Fusarium, Phomopsis species on the fruits.
Keywords: Persea americana; Colletotrichum sp.; Fusarium sp.; Phompsis sp.